2018
DOI: 10.1002/cem.3075
|View full text |Cite
|
Sign up to set email alerts
|

SVM for FT‐MIR prostate cancer classification: An alternative to the traditional methods

Abstract: In this paper, principal component analysis (PCA), successive projections algorithm (SPA), and genetic algorithm (GA) followed by support vector machines (SVM), combined with Fourier-transform mid-infrared (FT-MIR) spectroscopy were presented as complementary or alternatives tools to the traditional methods for prostate cancer screening and classification. These approaches were applied to analyze tissue samples, and their performances were compared within dependent SVM models and with traditional methods of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…The LDA supervised models are recurrent in several clinical studies of this nature, such as in cancer 36 , 37 and viral diseases 38 40 , because they work with processes with less complex characteristics. It is also common in the literature to find similar studies that expand the classifications to more robust models such as QDA 41 , 42 and SVM 43 , other researches seek to further expand the treatment of spectral samples, submitting them to these three types of techniques (LDA, QDA and SVM) and comparing the better accuracy results given the complexities of multivariate data 2 , 24 . This last approach is worked on and observed in this article.…”
Section: Discussionmentioning
confidence: 99%
“…The LDA supervised models are recurrent in several clinical studies of this nature, such as in cancer 36 , 37 and viral diseases 38 40 , because they work with processes with less complex characteristics. It is also common in the literature to find similar studies that expand the classifications to more robust models such as QDA 41 , 42 and SVM 43 , other researches seek to further expand the treatment of spectral samples, submitting them to these three types of techniques (LDA, QDA and SVM) and comparing the better accuracy results given the complexities of multivariate data 2 , 24 . This last approach is worked on and observed in this article.…”
Section: Discussionmentioning
confidence: 99%
“…The variables selected by these techniques can be used as input for the classification methods described previously, which is important since these techniques reduce the data size and collinearity, hence, improving the model accuracy and analysis time. Adaptations of PCA, PLS, SPA and GA (as feature extraction/selection techniques) to LDA, QDA, SVM, KNN and ANN (as classifiers) are well known [114][115][116] .…”
Section: Feature Extraction and Selectionmentioning
confidence: 99%
“…e results showed that the new method greatly compensated for the defects of the traditional methods [21]. Jung et al used the PCA-assisted SVM method for reliable channel reservoir characterization.…”
Section: Related Workmentioning
confidence: 99%